Mucociliary Clearance of Different Respiratory Conditions: A Clinical Study - Uzeloto, Juliana Souza [UNESP]; Ramos, Dionei [UNESP]; Silva, Bruna Spolador de Alencar [UNESP]; Lima, Mariana Belon Previatto de [UNESP]; Silva, Rebeca Nunes [UNESP]; Camillo, Carlos Augusto; Ramos, Ercy Mara Cipulo [UNESP] (Georg Thieme Verlag Kg, 2021)
Introduction Mucociliary clearance (MCC) is the first line of defense of the pulmonary system. Mucociliary clearance impairment may lead to increased risk of respiratory infections, lung injury, pulmonary repair problems, chronic dysfunctions and progression of respiratory diseases. Objective To characterize theMCC of active and passive smokers and individuals with chronic obstructive pulmonary disease (COPD) and compare the MCC behaviors between men and women of different age groups. Methods Patients with COPD (current smokers and ex-smokers) and apparently healthy individuals (current smokers, passive smokers and nonsmokers) were evaluated. All of the subjects underwent lung function and MCC evaluation (saccharin transport test [STT]). Smokers (with or without COPD) were questioned about the smoking history. Results A total of 418 individuals aged 16 to 82 years old, of both genders, were evaluated. The STT values of active and passive smokers were statistically higher than those of the control group (p < 0.01). Men of the control group had lower values of STT than active smokers (9.7 +/- 7.1 and 15.4 +/- 10.1minute, respectively, p < 0.01). In addition, higher MCC velocity was observed in women that are current smokers ( 11.7 +/- 6.8minute) compared with men (15.4 +/- 10.1minute) in this group (p = 0.01). Among the younger age groups (< 50 years old), only passive smokers presented higher STT in relation to the control group. Conclusion Passive and active smoking are factors that influence negatively the MCC, and passive smokers may present losses of this mechanism at a younger age. Additionally, male smokers present worse MCC than male nonsmokers.
Keywords: mucociliary clearance; saccharin; chronic obstructive pulmonary disease; smoking; passive smoking